Bioisosteric Replacement in the Search for Biologically Active Compounds: Design, Synthesis and Anti-Inflammatory Activity of Novel [1,2,4]triazino[2,3-c]quinazolines - Oleksandr Grytsak; Kostiantyn Shabelnyk; Hanna Severina; Victor Ryzhenko; Oleksii Voskoboinik; Igor Belenichev; Serhii Kovalenko; Valentyn Oksenych; Oleksandr Kamyshnyi (MDPI AG, 2024)
Background: Designing novel biologically active compounds with anti-inflammatory properties based on condensed quinazolines is a significant area of interest in modern medicinal chemistry. In the present study, we describe the development of promising new bioactive molecules through the bioisosteric replacement of a carbon atom with a sulfur atom in anti-inflammatory agents, specifically 3-methyl-2-oxo-2H-[1,2,4]triazino[2,3-c]quinazolin-6-yl)butanoate. Methods: Design and synthetic studies have led to the series of previously unknown substituted 2-[((3-R-2-oxo-2H-[1,2,4]triazino[2,3-c]quinazolin-6-yl)methyl)thio]carboxylic acids and their esters. These compounds were synthesized by reacting 6-chloroalkyl-3-R-2H-[1,2,4]triazino[2,3-c]quinazolin-2-ones with sulfanylalkyl carboxylic acids and their functional derivatives. The purity and structure of the obtained compounds were confirmed using a set of physicochemical methods, including elemental analysis, HPLC-MS, and 1H NMR spectroscopy. Molecular modeling, predicted toxicity, drug-likeness, and pharmacokinetics data were used to select compounds for evaluation of their effects on acute aseptic inflammation (carrageenan-induced paw edema test) and on markers of the inflammatory process. Results: The compound 2-((1-(3-methyl-2-oxo-2H-[1,2,4]triazino[2,3-c]quinazolin-6-yl)ethyl)thio)acetic acid (compound 2e) was identified as the most active anti-inflammatory agent (AA = 53.41%), demonstrating significant inhibition of both paw edema development and the generation of pro-inflammatory cytokines and mediators. Conclusions: Results from docking studies and analysis of "structure-affinity" correlations revealed that these compounds are promising candidates for further modification and detailed investigation of their anti-inflammatory activity